Design and Manufacture of a Flexible Pneumatic Soft Gripper - Jing Lei; Zhenghao Ge; Pengju Fan; Wang Zou; Tao Jiang; Liang Dong (Applied Sciences, 2022)
The soft robot has many degrees of freedom, strong environmental adaptability, and good human–computer interaction ability. As the end-effector of the soft robot, the soft gripper can grasp objects of different shapes without destructivity. Based on the theoretical analysis of the soft robot, the kinematics model of the flexible gripper and the theoretical model of the bending deformation of the air cavity were established. Accordingly, the relationship between the bending angle of the soft gripper and the air pressure was determined. Through the application of finite element software, the bending degree of the pneumatic network multi-cavity soft gripper was simulated, and the influence of structural parameters of soft actuator on bending deformation was determined. In addition, the 3D technology conducts the printing of soft gripper fixtures and molds, the injection molds the actuator, and the human–computer interaction interface controls the movement of the gripper. This paper proposes the control and monitoring of the soft gripper are realized through the electrical control module, the air circuit control module, and the sensor group module, and the size of the airflow velocity can be controlled by PWM DC speed regulation. The adaptability of the soft gripper in grasping objects was verified. The results shows that the software gripper possesses good flexibility and can better grasp objects of different shapes.